2022
DOI: 10.1002/ehf2.13912
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant myocarditis caused by immune checkpoint inhibitor: a case report and possible treatment inspiration

Abstract: Immune checkpoint inhibitors (ICIs) have become a new hope for many patients with advanced cancer by blocking tumour immune evasion. However, with the widespread use of ICIs, immune-related adverse events (irAEs) have also been discovered and reported increasingly. Immune-related myocarditis, the most dangerous one of irAEs, still has high mortality in the context of the current treatment. We report the case of a 60-year-old female with fulminant myocarditis induced by ICIs, which caused her to experience freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that sacubitril/valsartan (an angiotensin receptor neoplasia inhibitor) improves cardiovascular risk, sudden death, or reduced ejection fraction (HFrEF) in heart failure. 17 Therefore, we simultaneously administered sacubitril/valsartan. Unfortunately, the patient’s condition did not improve.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sacubitril/valsartan (an angiotensin receptor neoplasia inhibitor) improves cardiovascular risk, sudden death, or reduced ejection fraction (HFrEF) in heart failure. 17 Therefore, we simultaneously administered sacubitril/valsartan. Unfortunately, the patient’s condition did not improve.…”
Section: Discussionmentioning
confidence: 99%